MEKANISME TATA KELOLA PERUSAHAAN, PERSAINGAN PASAR PRODUK DAN KINERJA PERUSAHAAN: MEKANISME TATA KELOLA PERUSAHAAN, PERSAINGAN PASAR PRODUK DAN KINERJA PERUSAHAAN - Ika Pratiwi; Retno Dwi Irianto (Jurnal Proaksi, 2021)
The board of directors represents the interests of shareholders and monitors management on a wide range of agency matters. Board independence remains an important aspect of board monitoring among regulators worldwide. Several theoretical studies investigate the effect of corporate governance and some effects of competition on firm performance but the aim of this study is to examine the effect of corporate governance mechanisms on firm performance and to examine the effect of interaction between corporate governance mechanisms and product market competition on firm performance. The population in this study are all companies listed on the Indonesia Stock Exchange in 2017-2019. The variables of corporate governance mechanisms used in this study are independent commissioners and managerial ownership and product market competition as moderating variables. The sampling method in this study was purposive sampling. The company criteria used are companies listed on the IDX in 2017-2019 except for the financial sector. There are 711 data that fall into the criteria. Multiple regression analysis and moderate regression analysis (MRA) were used as analysis techniques. The results showed that independent commissioners had no effect on company performance, while managerial ownership had a positive effect on company performance. The results of the interaction effect of corporate governance mechanisms and product market competition on company performance indicate that product market competition has a significant positive effect on the relationship between independent commissioners and company performance. Product market competition has a significant positive effect on the relationship between managerial ownership and company performance on company performance. Keywords: Firm Performance, Independent Commissioner, Managerial Ownership, Product Market Competition